Membaca Fenomena Menguatnya Perayaan “Islamisasi” di Indonesia Pasca Reformasi - Dian Dwi Jayanto (Jurnal Kawistara, 2020)
The strengthening of Islamization (Islamisasi) or the revival of religious awakening in the post-reform Indonesia has become an appealing topic to be studied by social scientists. Islamization, in this study, is not defined in terms of the discourse of religious political relations (such as relations of state and religion), but refers to the existence of social religious expressions which are marked by considerable exploration to form a new meaning of Islam (Islamization) which involves various elements, especially capitalism and modernity. This paper provides an overview of how social scientists see the phenomenon of Islamization in the post-reform Indonesia. This overview is important in order to discuss the viewpoints or better known as "standing positions" of scientists in seeing the phenomenon of Islamization in Indonesia. This paper uses a literature study in the form of collecting various relevant studies related to the analysis of Islamization in the post-reform Indonesia. It then simplifies a number of selected studies from various scientific writings and finds various perspectives, including ones which see this phenomenon as a symptom of radicalism, a form of the success of commodification of Islam. Another perspective makes use of the concept of Post-Islamism and links it with the hybrid identity concept. In the end, this paper concludes that there are two big perspectives, besides the mainstream perspective of radicalism and terrorism, namely the commodification of Islam and Post-Islamism. This research argues that these two perspectives can be used as a basis for thinking in reading the dynamics of increasing social-religious expression in Indonesia with different analytical levels.